MATERNAL AND FETAL OUTCOME IN UNDIAGNOSED AND DIAGNOSED SINGLETON BREECH PRESENTATION AT TERM - Zahoor, Shafaq; Faiz, Nasreen Ruby (Journal of Postgraduate Medical Institute, 2011)
Objective: To find out the maternal and fetal outcome in undiagnosed and diagnosed singleton breech presentation at term. Material and Methods: This study was conducted at Lady Reading Hospital, Peshawar from 1st July 2000 to 30th June 2001 on patients presenting with singleton term breech. Multiple pregnancy and preterm breech were excluded. Information regarding,age, address, parity, gestational age, physical and vaginal examination, ultrasound findings, mode of delivery, any specific procedures performed including external cephalic version (ECV) was collected. Demographic variables and obstetrical outcome were observed in diagnosed and undiagnosed breech cases.Diagnosed breech cases were diagnosed antenatally and proper management plan decided, while undiagnosed breech cases were unbooked who came to hospital for 1st time in labour. Results: Out of 203 cases, 163 (80.29%) patients presented with undiagnosed breech and 40(19.71%) had been diagnosed in antenatal clinic. Out of 163 undiagnosed cases, 137 (84.1%) had successful vaginal breech delivery (VBD), 22 (13.5%) cases had caesarean section (CS), three (1.8%) had subtotal hysterectomy for rupture uterus and 1 (0.6%) with successful ECV had normal vaginal delivery (NVD). Among 40 diagnosed cases, 8(20%) had successful VBD, 22 (55%) had CS and 10 (25%) had successful ECV followed by NVD. There was no statistical significant difference in short term neonatal outcome, neonatal morbidity and mortality among both groups. Maternal morbidity was lower in vaginally delivered undiagnosed breech cases than in those delivered by caesarean section.In diagnosed group maternal morbidity was the same regardless of mode of delivery. Conclusion: Good prenatal care is essential to reduce undiagnosed breech cases at term. ECVreduces the incidence of Breech Presentation at delivery. In selected cases VBD is a safe option.